(untitled) (Scientific journal of the Fergana State University, 2026)
The purpose of this research is to determine and examine the psychological and pedagogical elements that influence college students’ capacity for autonomous language acquisition. A comprehensive literature review, classroom observations, student surveys, and interviews were all used in the study. The results show that the success of autonomous learning is significantly influenced by students’ intrinsic motivation, self-control, time management, and instructor help in the form of constructive criticism. The use of creative teaching methods and the development of a positive learning atmosphere also greatly boost students’ enthusiasm in independent study. The study’s result highlights how crucial it is to combine pedagogical and psychological elements to guarantee successful independent learning in language institutions.